English and Local Language Preservation in East Nusa Tenggara: A Study of Pre-Service English Teachers’ Attitudes and Practices - Ate, Christmas Prasetia; Muliani, Muliani (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The widespread adoption of English in Indonesia has raised concerns about its impact on local language sustainability, especially in multilingual, postcolonial regions such as East Nusa Tenggara. This study investigates how English learning can coexist with local language preservation by addressing three key issues: (1) students’ attitudes toward English and local languages, (2) the use of these languages across different domains, and (3) strategies proposed for promoting linguistic coexistence. Nineteen sixth-semester English Education students from Citra Bangsa University were selected as participants, given their future roles as language educators and policy influencers. Using a qualitative approach that included semi-structured interviews, focus group discussions, and surveys, the study found a dual but sometimes conflicting orientation. The results show that participants acknowledged the instrumental value of English for education and career advancement (89%) while affirming the cultural importance of local languages (95%). In terms of usage, local languages remained dominant in-home domains (65%) but were marginalized in academic settings (5%) and peer interactions (21%), revealing a domain-specific pattern shaped by perceived language utility. To bridge this gap, participants suggested strategies such as bilingual education models (74%), community-driven language initiatives (63%), and culturally inclusive curricula. However, 47% expressed skepticism toward government-led solutions, citing lack of relevance and implementation barriers. The findings indicate that sustainable multilingualism is possible through intentional, context-sensitive strategies. The study recommends reorienting teacher education to support multilingual pedagogies, integrating local knowledge, and fostering collaboration between grassroots efforts and institutional frameworks to ensure balanced language ecologies.